2013
DOI: 10.3389/fpsyt.2012.00116
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Functional Connectivity in Late-Life Depression: Higher Global Connectivity and More Long Distance Connections

Abstract: Functional magnetic resonance imaging recordings in the resting-state (RS) from the human brain are characterized by spontaneous low-frequency fluctuations in the blood oxygenation level dependent signal that reveal functional connectivity (FC) via their spatial synchronicity. This RS study applied network analysis to compare FC between late-life depression (LLD) patients and control subjects. Raw cross-correlation matrices (CM) for LLD were characterized by higher FC. We analyzed the small-world (SW) and modu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 77 publications
7
50
3
Order By: Relevance
“…Older depressed individuals, regardless of their cognitive impairment statuses, showed reduced local efficiency, which is reflective of deficient segregation of functional neural processing and lower levels of local connectedness. Our results of similar functional integration measures between non-depressed aMCI, cognitively normal LLD and control participants are consistent with recent investigations 21 23. However, Wang et al 24 revealed a longer characteristic path length in patients with aMCI; their sample was younger and more cognitively impaired than ours.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Older depressed individuals, regardless of their cognitive impairment statuses, showed reduced local efficiency, which is reflective of deficient segregation of functional neural processing and lower levels of local connectedness. Our results of similar functional integration measures between non-depressed aMCI, cognitively normal LLD and control participants are consistent with recent investigations 21 23. However, Wang et al 24 revealed a longer characteristic path length in patients with aMCI; their sample was younger and more cognitively impaired than ours.…”
Section: Discussionsupporting
confidence: 92%
“…The regions with high betweenness centrality that are identified in our control group (posterior cingulate, insula, inferior frontal gyrus, VMPFC and cuneus) are in accordance with the highly connected hubs reported in previous functional network studies (see online supplementary table S1) 21 23. These hubs, which are essential for effective communication and robust network performance, are also critical nodes of the default mode and SNs, as extensively described in the literature 38.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Together, these additional hippocampal networks for past and future thinking are broadly consistent with the changes in restingstate connectivity commonly observed in depression (e.g., Bohr et al, 2013;Zhou et al, 2010;Zhu et al, 2012). Our findings suggest that, in depressed individuals, enhanced connectivity of both task-relevant networks (i.e., the default network) and recruitment of supplementary networks (i.e., dorsal attention network) can support successful autobiographical event generation.…”
Section: Discussionsupporting
confidence: 75%
“…Functional connectivity reductions between the mediodorsal nucleus and cerebellum were observed in SCZ but not in BD. Graph metric properties of the brain have also recently been assessed in late life depression [337]: Here connections spanning longer euclidean distances were increased after the onset of late life depression. Interestingly, this change did not influence the small world index.…”
Section: Chaptermentioning
confidence: 99%